Projecting climate migration in Bangladesh using agent based modeling and climate data - O'Neill, Orla; Velders, Guus J. M.; Mallick, Bishawjit; Best, Kelsea (Frontiers in Climate, 2025)
IntroductionThere is fear that climate change will lead to the displacement of millions of people in the next 100 years. This has led to increased academic interest in estimating the trends of climate-related migration. Bangladesh is particularly vulnerable to climate change and is very likely to experience mass climate migration before the end of the century. Efforts have been made to forecast this climate migration using agent based modeling. Less attention has been paid to how the physical climate is represented in these models.MethodsWe address this gap, by developing an agent based model which takes dynamic climate input from climate models, i.e. data on temperature, precipitation and wind speed. It translates climate scenario data from the Shared Socioeconomic Pathways (SSPs) into a likelihood that a region in Bangladesh will experience extreme weather (heatwaves, floods, and cyclones) and finds the possible migration outcomes. It can run on an upazila level, the smallest administrative division in Bangladesh.ResultsThe model shows that there will be an accumulative number of over 22 million internal climate migrants in Bangladesh by 2050, with most of the migrants originating from the center of the country and migrating to other upazilas in the center and the southeast.DiscussionThe inclusion of different types of extreme weather events is used to try to project the spatial movement of migrants. The projected number of migrants found is much greater than other studies in this area, but the locations that they move between remains the same.